Midnight dunes - Griffin, Laura, 1973- (Griffin, Laura, 1973- Texas murder files, 2022)
"When the shocking discovery of a murdered woman's body disturbs the tranquility of tourist season, the police detective in charge of the puzzling case must work alongside the new filmmaker in town to pursue every lead in the new romantic thriller from New York Times bestselling author Laura Griffin. After a scandal derails her television reporting career, Macey Burns comes looking for a change of pace in Lost Beach, Texas. She's ready to focus on her first passion--documentary filmmaking--and has a new job working for the island's tourism board, shooting footage of the idyllic beachside community. Her plans for a relaxing rebound are dashed when she realizes the cottage she's renting belonged to the woman whose body was just found in the sand dunes. Detective Owen Breda is under intense pressure to solve this murder. Violent crimes are rising in his small town, and he can't stand to see anyone else hurt...especially not the beautiful documentarian who keeps showing up at the precinct. With the clock ticking, cameras rolling, and body count climbing, Macey and Owen must use all their resources to find the killer without getting caught in the crosshairs."--provided by publisher.